Applicability of a Heat Recovery Ventilator Retrofit in a Vancouver Residential House - Bo Li; Wei Yue; Fitsum Tariku (Energies)
Heat recovery systems are increasingly recognized as key energy conservation measures in residential buildings. But their effectiveness is highly sensitive to operational conditions. This study used a calibrated OpenStudio simulation, which is validated against monthly utility data, to investigate the feasibility of implementing a heat recovery ventilator in an existing single-detached house in Vancouver under two scenarios: existing passive ventilation without a heat recovery ventilator versus the proposed balanced mechanical ventilation with a heat recovery ventilator. The findings indicate that employing an HRV in an existing house lacking balanced ventilation would lead to higher annual space heating energy consumption (75.49 GJ electricity and 56.70 GJ natural gas with HRV compared to 73.64 GJ and 52.70 GJ, respectively, without an HRV). Therefore, for existing houses without balanced ventilation, improving the existing building envelope’s airtightness through retrofits should always be carried out before installing a heat recovery ventilator. Additionally, the heat recovery ventilator should be appropriately sized to compensate for any shortfall in natural infiltration to ensure the sufficient indoor air quality while minimizing the outdoor air-induced space heating energy usage. Furthermore, the recommended break-even point of the infiltration rate for the house studied in this work to avoid increased space heating energy use due to the retrofit with a heat recovery ventilator is 0.281 air change per hour.